METABOLIC DYSFUNCTIONS CAUSED BY EARLY FRUCTOSE INGESTION ARE PREVENTED IN CONCURRENTLY EXERCISED ADULT MALE RATS - Letícia F. Barbosa; Sandra S. Silveira; Christian M. Mendes; Veridiana M. Moreira; Paulo C. F. Mathias (Arquivos do Mudi, 2023)
This study evaluated whether fructose ingestion at adolescence programs the development ofmetabolic syndrome (MetS) in adult rats and whether moderate-intensity combined exercisecan attenuate fructose-induced MetS compounds. Pubertal rats were trained on a treadmill(55-65% VO 2max ), 3 times/week, 44 min/session, for one month. They were allocated into fourgroups: sedentary control (SC), trained control (TC), sedentary fructose (SF), and trainedfructose (TF). Groups F ingested 10% fructose. Food intake (AI) and body weight (BW) weremeasured weekly. At 60 and 120 days of age, metabolic parameters were evaluated. Fructoseintake mainly affected animals in adult life, and these changes were related to glucoseintolerance (p=0.001), periepididymal fat (p<0.03), and increase in total cholesterol (TC) (p<0.001), triglycerides (TAGs) (p<0.0001) and insulin (p<0.0001) levels. Early physicalexercise was able to decrease periepididymal (p<0.003) and retroperitoneal (p<0.0002)adipose tissue, TC levels (p<0.0001) and glucose tolerance (p=0.21). Rats that receivedcombined treatments during adolescence showed low glycemia (p=0.003) and insulinemia(p<0.0001) during the intraperitoneal glucose tolerance test (ipGTT). HOMA-IR (p=0.02) andTYG (p=0.0003) scores also improved in these rats. We conclude that early ingestion of 10%fructose was effective in programming adult rats to MetS, and simultaneous moderateexercise attenuated these aggressions, causing changes in glycemic homeostasis and lipidmetabolism.